Sosialisasi Sistem Pemeliharaan Ayam untuk Menghasilkan Daging dan Telur Organik di Lembah Hijau Desa Ijobalit, Labuhan Haji Lombok Timur - Tamzil, Mohammad Hasil; Sarjan, Muhamad; Kisman; Iqbal, Muhammad Syamsu; Lestari, Dewi Putri; Dewi, Suprayanti Martia (Universitas Mataram, 2025)
This community service program aims to enhance understanding of the poultry farming system for producing organic meat and eggs in the Lembah Hijau of Ijobalit Village, Labuhan Haji, East Lombok. This initiative was conducted in collaboration with the Sustainable Development Resources Institute (LSPB), the University of Mataram, and the Lembah Hijau Tourism Park Management of Ijobalit Village, East Lombok. The program was implemented through lectures, discussions, and direct field assessments of land with the potential for organic poultry farming. The activities proceeded as planned.